193k views
1 vote
VII. Find all the zeros of the function.

10. f(x)=x³+3x² – 6x − 8
-
11. f(x)=x³ – x² + 9x− 9
12 f(x)=x²-x³-5x² +9x-4
x4
X

VII. Find all the zeros of the function. 10. f(x)=x³+3x² – 6x − 8 - 11. f(x)=x³ – x-example-1

1 Answer

2 votes

Answer:

10. x=2 v x =-1 v x=-4

11. x=1

12 x=1 v x=(-1-√17)/2 v x=(-1+√17)/2

Explanation:

10.

f(x)=x³+3x²-6x-8

{-1,1,-2,2,-4,4,-8,8} one of these can be zeros of the function

f(2)=2³+3*2²-6*2-8=8+12-12-8=0

x=2 =>x-2=0

f(x)=(x-2)(x²+kx+4)

(x-2)(x²+kx+4)=x³+3x²-6x-8

x³+kx²+4x-2x²-2kx-8=x³+3x²-6x-8

x³+(k-2)x²+(4-2k)x-8=x³+3x²-6x-8

k-2=3 ∧ 4-2k=-6

k=5 ∧ -2k=-10

k=5 ∧ k=5

f(x)=(x-2)(x²+5x+4)

1)

4=1*4=2*2

1+4=5

x²+5x+4=x²+x+4x+4=x(x+1)+4(x+1)=(x+1)(x+4)

f(x)=(x-2)(x+1)(x+4)

f(x)=0

(x-2)(x+1)(x+4)=0

x-2=0 v x+1=0 v x+4=0

x=2 v x =-1 v x=-4

or 2)

f(x)=(x-2)(x²+5x+4)

f(x)=0

(x-2)(x²+5x+4)=0

x-2=0 v x²+5x+4=0

x=2 v x²+5x+4=0

Δ=b²-4ac

b=5 a=1 c=4

Δ=5²-4*1*4

Δ=9

√Δ=3

x=(-b-√Δ)/2a v x=(-b+√Δ)/2a

x=(-5-3)/2 v x=(-5+3)/2

x=-4 v x=-1

x=2 v x=-4 v x=-1

11

f(x)=x³ – x² + 9x− 9

f(x)=0

x³ – x² + 9x− 9=0

x²(x-1)+9(x-1)=0

(x-1)(x²+9)=0

x²+9>0 no solution in Real number

x-1=0

x=1

12

f(x)=x⁴-x³-5x²+9x-4

{-1,1,-2,2,-4,4} one of these can be zeros of the function

f(1)=1⁴-1³-5*1²+9*1-4=1-1-5+9-4=0

x=1

x-1=0

f(x)=(x-1)(x³+px²+qx+4)

(x-1)(x³+px²+qx+4)=x⁴-x³-5x²+9x-4

x⁴+px³+qx²+4x-x³-px²-qx-4=x⁴-x³-5x²+9x-4

x⁴+(p-1)x³+(q-p)x²+(4-q)x-4=x⁴-x³-5x²+9x-4

p-1=-1 ∧ q-p=-5 ∧ 4-q=9

p=0∧ q-0=-5 ∧ -q=5

p=xx0 ∧ q=-5 ∧ q=-5

p=0, q=-5

1)

f(x)=(x-1)(x³-5x+4)

x³-5x+4=x³-x-4x+4=x(x²-1)-4(x-1)=x(x-1)(x+1)-4(x-1)=(x-1)[x(x+1)-4]=(x-1)(x²+x-4)

f(x)=(x-1)(x-1)(x²+x-4) f(x)=0

(x-1)²(x²+x-4) =0

x-1=0 v x²+x-4=0

x=1 v x²+x-4=0

Δ=b²-4ac

b=1 a=1 c=-4

Δ=1²-4*1*(-4)

Δ=17

√Δ=√17

x=(-b-√Δ)/2a v x=(-b+√Δ)/2a

x=(-1-√17)/2 v x=(-1+√17)/2

x=1 v x=(-1-√17)/2 v x=(-1+√17)/2

or 2)

f(x)=(x-1)(x³-5x+4)

g(x)=x³-5x+4

{-1,1,-2,2,-4,4} one of these can be zeros of the function

g(1)=1³-5*1+4=1-5+4=0

x=1

x-1=0

g(x)=(x-1)(x²+rx-4)

(x-1)(x²+rx-4)=x³-5x+4

x³+rx²-4x-x²-rx-4=x³-5x+4

x³+(r-1)x²+(-4-r)x-4=x³-5x+4

r-1=0 ∧ -4-r=-5

r=1 ∧ -r=-1

r=1

g(x)=(x-1)(x²+x-4)

g(x)=0

(x-1)²(x²+x-4) =0

x-1=0 v x²+x-4=0

x=1 v x²+x-4=0

Δ=b²-4ac

b=1 a=1 c=-4

Δ=1²-4*1*(-4)

Δ=17

√Δ=√17

x=(-b-√Δ)/2a v x=(-b+√Δ)/2a

x=(-1-√17)/2 v x=(-1+√17)/2

x=1 v x=(-1-√17)/2 v x=(-1+√17)/2

User Wosh
by
5.3k points